ANTIBACTERIAL EFFECTIVENESS OF LIME LEAVES (Citrus hystrix DC) ETHANOL EXTRACT ON Enterococcus faecalis BACTERIA : Efektivitas Antibakteri Ekstrak Etanol Daun Jeruk Purut (Citrus Hystrix Dc) Terhadap Bakteri Enterococcus faecalis - Ratih Widyasari; Willy Hadinata Halim; Atia Nurul Sidiqa; Dewa Made Wedagama (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: Endodontic treatment failure can be caused by the bacterium E. faecalis, which has a prevalence of up to 90%. E. faecalis is difficult to eradicate because it forms a biofilm to defend itself against antibacterial agents. Lime leaves are one of the many herbal products available in Indonesia (Citrus hystrix DC). Lime leaf extracts include antibacterial components such as essential oils, phenolics, alkaloids, saponins, and tannins. The purpose of this study was to investigate the antibacterial activity of lime leaf extract against E. faecalis bacterium. Material and Methods: The agar diffusion technique was used for four experimental groups, using lime leaf extract at 4% (group 1), 8% (group 2), and 16% (group 3) as the negative control. Each group was repeated six times on Muller Hinton Agar (MHA) medium with a paper disc, and the diameter of the inhibitory zone was measured with a caliper. Results and Discussions: The results revealed that a 4 % concentration of lime leaf extract had an average inhibition zone diameter of 7.31 mm, an 8 % concentration had an average inhibition zone diameter of 8.59 mm, and a 16 % concentration had an average inhibition zone diameter of 11.41 mm. The difference in the inhibition zone was statistically significant (p= 0,000) evaluated using the one-way ANOVA. Conclusion: It can be concluded that lime leaf extract is antibacterial potential against E. faecalis bacteria in the endodontic treatment.